Salmonella serotypes isolated in geckos kept in seven collections in southern Italy. (9th January 2018) - Russo, T. P.; Varriale, L.; Borrelli, L.; Pace, A.; Latronico, M.; Menna, L. F.; Fioretti, A.; Dipineto, L.
Abstract : Objectives: Reptiles are considered an important reservoir of Salmonella species. This study evaluated the prevalence of Salmonella species in different species of gecko kept as pets in Italy. Materials and Methods: Faecal swab samples were collected from 70 clinically healthy geckos and examined for Salmonella species by culture that were then serotyped. Results: Salmonella species were isolated from 24 of 70 (34·3%) samples. Eighteen isolates expressed resistance to ceftazidime and four isolates to ampicillin. Clinical Significance: Salmonella spp. can be isolated from apparently healthy captive gecko which should be considered as a potential source of infection for humans and other companion animals.